(untitled) (ALPHA. Journal of Arts, Literature and Philosophy, 1998)
Mario Vargas Llosa, one of the giants of the so-called “Boom” of Latin American literature, has spent a year in Germany for the second time, this time as a guest of the Deutsche Akademie, and is now preparing his suitcases to return to his usual residence. His first long stay in this country came after the dramatic months of the electoral campaign in Peru and his defeat in the runoff vote, which resulted in the current president Alberto Fujimori emerging as the victor. Invited by the Wissenschaftskolleg, the writer was able to spend the academic year 1991/92 in Germany, away from the political turmoil of his country, and summarize his reflections on the electoral campaign in the book “El pez en el agua” (“The Fish in the Water”).